Przesyłanie danych i obrazu w bezprzewodowych sieciach komputerowych - Nikodem, Ryszard (Voice and video transfer in wireless computer networks, 2006)
The article concerns audio and video transfer in wireless computer networks. Centralized architecture of WLAN and 802.1 le standard are described. Other methods, as guarantied throughput of access network, quality of service and Voice over IP in WLAN networks, are also mentioned. Trends and new technologies like WiMAX, Distributed Admission Control and mesh topology for wireless networks are discussed in the last section.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1134, s. 116-122